Bradyrhizobium Lipid A: Immunological Properties and Molecular Basis of Its Binding to the Myeloid Differentiation Protein-2/Toll-Like Receptor 4 Complex - Lembo-Fazio, Luigi; Billod, Jean-Marc; Di Lorenzo, Flaviana; Paciello, Ida; Pallach, Mateusz; Vaz-Francisco, Sara; Holgado, Aurora; Beyaert, Rudi; Fresno, Manuel; Shimoyama, Atsushi; Lanzetta, Rosa; Fukase, Koichi; et al. (Frontiers in Immunology, 2018)
Lipopolysaccharides (LPS) are potent activator of the innate immune response through the binding to the myeloid differentiation protein-2 (MD-2)/Toll-Like Receptor 4 (TLR4) receptor complex. Although a variety of LPSs have been characterized so far, a detailed molecular description of the structure-activity relationship of the lipid A part has yet to be clarified. Photosynthetic Bradyrhizobium strains, symbiont of Aeschynomene legumes, express distinctive LPSs bearing very long chain fatty acids with a hopanoid moiety covalently linked to the lipid A region. Here, we investigated the immunological properties of LPSs isolated from Bradyrhizobium strains on both murine and human immune systems. We found that they exhibit a weak agonistic activity and, more interestingly, a potent inhibitory effect on MD-2/TLR4 activation exerted by toxic enterobacterial LPSs. By applying computational modelling techniques, we also furnished a plausible explanation for the Bradyrhizobium LPS inhibitory activity at atomic level, revealing that its uncommon lipid A chemical features could impair the proper formation of the receptorial complex, and/or has a destabilizing effect on the pre-assembled complex itself.